The Concept of God and Its Role in the Semantics of Divine Attributes - Meysam Molaei; Mohammadali Abdollahi (پژوهشنامه فلسفه دین, 2014)
This article does not attempt to answer all questions against the semantics of the attributes of God, Even not going to answer that,” what is the meaning of Omniscient/ Omnipotent/Perfectly Good?” Rather, we want to provide with a way which shows how the properties mentioned above can be defined or judged. We assert that for the semantics of the properties of God, one has to consider the theists’ Understanding of God. On the traditional understanding of monotheistic religions, especially Islam, we can define God as the Absolute Being. The conceptual analysis of this notion leads us to the notion of God as extremely Perfect Being. By this notion, we will try to analyze properties of God. According to this notion, when a theist claims that God is Omniscient, Omnipotent and Perfectly Good, he means that God has knowledge, power and goodness in their most perfect sense. This implies that He is a Perfect Being, and His perfection can be explained only when He has this properties necessarily or simply and Immutably. To reach these results, first we will provide with an explanation of the properties ”Omniscient”, “Omnipotent” and” Perfectly Good”. According to this explanation, the main focus must be on the concept of 'absolute'. As a result, we need to know how this concept should be applied. Then, concentrating on the concept of God as the absolute and its interpretation as extremely perfect being will provide us with an analysis of this concept based on which a methodology of semantic analysis of the aforementioned properties will be determined.